The epidemiology of aging - Newman, Anne. (Springer Netherlands, 2012)
The average age of the world’s population is increasing at an unprecedented rate and this increase is changing the world. This “Silver tsunami” emphasizes the need to provide advanced training in epidemiology and increase the cadre of experts in the study of aging. This book is designed to summarize unique methodological issues relevant to the study of the epidemiology of aging, biomarkers of aging and the biology/physiology of aging and in-depth discussions of the etiology and epidemiology of common geriatric syndromes and diseases. Contributing authors in the book represent many disciplines, not only epidemiology and clinical geriatrics, but also demography, health services, research, cardiovascular disease, diabetes, psychiatry, neurology, social services, musculoskeletal diseases and cancer. The aim of the book is to provide a broad multidisciplinary background for any student/researcher interested in aging. The material in the book is organized and comprehensive. It represents the most up-to-date information on the scientific issues in aging research written by academics who specialize in research and training in the broad field of aging. The structure and organization of the book reflects our course series in the Epidemiology of Aging starting with the broad issues of demography and methodology, and then addressing specific health conditions and geriatric conditions common to older persons. Section 1 Methods -- 1 The demography of aging -- 2 Conducting case-control and cohort studies in older adults -- 3 Study design: randomized controlled trials.– 4 Target populations, recruitment, retention, and optimal testing methods: methodological issues for studies in the epidemiology of aging -- 5 Nursing home research -- 6 Use of proxies and informants -- 7 assessing functional status and disability in epidemiologic studies -- 8 Comorbidity and multimorbidity -- 9 Measurement of social factors in aging research -- 10 Lifecourse epidemiology and aging -- 11 Using epidemiology to inform community health programs and policy -- Section 2 aging, geriatric syndromes and common conditions -- 12 Understanding the aging process using epidemiologic approaches -- 13 Genetics of human longevity and healthy aging -- 14 Aging, infection and immunity -- 15 Nutritional epidemiology in aging -- 16 Body composition and aging -- 17 Epidemiology of falls and mobility disorders -- 18 Medication use in older adults -- 19 Visual impairment -- 20 Age-related hearing loss -- 21 Oral health and the epidemiology of oral disease in older adults -- 22 Epidemiology of cancer and aging -- 23 The epidemiology of coronary artery disease in older adults -- 24 Asthma and copd -- 25 The impact of diabetes in older adults -- 26 The pre-diabetic, insulin-resistant state -- 27 Chronic kidney disease -- 28 Osteoporosis -- 29 Epidemiology of osteoarthritis -- 30 stroke epidemiology and prevention -- 31 Dementia and alzheimer’s disease -- 32 Depression and other common mental health disorders in old age.